Design And Fabrication Of Fatigue Test Rig And Preliminary Investigation On Flax Composite Beam. (2018) - Nagabhooshanam, N.; Baskar, S.; Nagarajan, P.K.; kumar, K. Sathish
Abstract: Reinforced polymer laminates are used increasingly as structural parts in automobile, aircraft and navel industries due to their excellent mechanical characteristics for relatively low density when compared to the conventional materials and therefore much information on mechanical properties are necessary. Composite materials behaviour subjected to fatigue load is very complex due to its non-homogeneous and anisotropic properties. So it is very important to understand the fatigue behaviour of FRP laminates to extend its usage for various applications in the current industries. Main objective of the project is to understand the fatigue behaviour of the composite laminates when it is subjected to fully reversed bending fatigue cycle. In this case it is very important to develop a specific test setup and approach to perform fatigue test avoid the utilization of expensive test methods available in the market. So a fatigue test rig was designed and developed for this project. Fatigue behaviour of composite laminates was studied in terms of stiffness degradation by performing experimental static deflection test on the test specimen before and after subjecting it to the fatigue load.